Human Milk Feeding Patterns at 6 Months of Age are a Major Determinant of Fecal Bacterial Diversity in Infants. (November 2021) - Sugino, Kameron Y.; Ma, Tengfei; Kerver, Jean M.; Paneth, Nigel; Comstock, Sarah S.
Background: Maternal pre-pregnancy obesity and human milk feeding have been associated with altered infant gut microbiota. Research aim: Determine the relationships between maternal pre-pregnancy BMI, human milk exposure, and their influence on the infant microbiota simultaneously. Methods: This was a cross-sectional study of infants at 6 months of age ( N = 36), a time when many infants are fed a mixed diet of human milk and other foods. Fecal samples and participant information were collected from a subset of dyads enrolled in two related prospective cohorts (ARCHGUT and BABYGUT ) in Michigan. Sequencing the V4 region of the 16S gene was used to analyze fecal bacterial samples collected from 6-month-old infants. Participants were grouped into four categories designated by their extent of human milk exposure (100%, 80%, 50%–80%, ≤ 20% human milk in the infant diet) and by maternal pre-pregnancy BMI category (normal, overweight, obese). Results: Fewer participants with pre-pregnancy obesity were breastfeeding at 6 months postpartum compared to non-obese participants (35.7% and 81.8%, respectively). In univariate analyses, maternal pre-pregnancy BMI and human milk exposure were both significantly associated with alpha and beta diversity of the infant microbiota. However, in multivariate analyses, human milk exposure accounted for 20% of the variation in alpha diversity, but pre-pregnancy BMI was not significantly associated with any form of microbiota diversity. Conclusions: The proportion of the infant diet that was human milk at 6 months was the major determinant of alpha and beta diversity of the infant. Maternal obesity contributes to the gut microbiota by its association with the extent of human milk feeding.